3D MODEL BEDROOM CONCEPT USING MULTIMEDIA DEVELOPMENT LIFE CYCLE (MDLC) - Pratama, Jimmy; Stephanie; Syahputra, Bayu (UNIVERSITAS STEKOM, 2024)
Interior is the arrangement of the inner room with the aim of meet the needs of the facility, namely the element of functionality and the aesthetic element of beauty. However, not all rooms can implement both elements because of a lack of knowledge about rooms and interiors. Interior design also can’t be done carelessly, especially the bedroom. This is because the bedroom can give an impression which is an important principle for users, namely the level of comfort and type of activity. Therefore, the aim of this research is to provide the visualization of bedroom interior in 3D animation to be a source of reference for users. This research use R&D (Research and Development) method, which use a qualitative approach by interviewing 30 respondents as a research method and by Multimedia Development Life Cycle (MDLC) method as a development method. The result of this research is the visualization of bedroom interior in 3D animation that can be used as a reference source for users to design bedroom interiors.